Influence of COVID-19 Vaccination Covaxin on Menstrual Cycle among Adolescent Healthy Schoolgirls in South India - Krithika Kumar; Gowri Dorairajan; Palanivel Chinnakali; Vignesh Durai (Indian Journal of Public Health)
This study was undertaken to assess the change in menstrual cycle interval, duration, amount of flow, and new onset of pain after the first and second dose of Covaxin vaccination among adolescent schoolgirls aged 15–18. Informed assent and parental consent were taken. Two hundred and thirty-three participants were approached and the response rate was 57.5%. One hundred and thirty-four respondents who participated had received at least one dose, and 116 among them had received both doses of Covaxin. About 17% of the girls had a body mass index above 25 kg/m2. We did not find any clinical or statistically significant difference in the interval or flow duration. About 19% reported new-onset mild pain during the menstrual cycle bleeding phase.